Prehabilitation for Patients with Cancer Undergoing Radiation Therapy: a Scoping Review - Marignol, Laure (My University, 2024)
Aims: Prehabilitation is a process of identifying and assessing factors that could compromise the physical and psychological health of patients undergoing cancer treatment and implementing an intervention to combat such concerns. The use of prehabilitation in cancer surgery has yielded positive outcomes in rectal, lung and abdominal cancers. Prehabilitation strategies have potential to improve the management of patients receiving radiation therapy or chemoradiation. The aim of the present study was to map the evidence of the assessment and evaluation of prehabilitation for radiation therapy patients. Materials and methods: A database search using EMBASE and PubMed was conducted. The PRISMA guidelines were adhered to. Keywords included prehabilitation, radiation therapy/radiotherapy, chemoradiotherapy/chemoradiation, intervention and exercise. Types of prehabilitation strategy, their purposes and impact, according to cancer site, were analysed. Results: Prehabilitation is most commonly evaluated in head and neck cancer, whereby unimodal, physical interventions manage dysphagia. Prehabilitation for lung cancer demonstrated its ability to widen treatment options for patients. Physical prehabilitation is administered to combat adverse effects of neoadjuvant chemoradiation therapy in patients with rectal cancer. Conclusion: Prehabilitation is adaptive and tailored to specific patient and site needs; thus it is applied across a wide range of cancer sites. More interventions by which radiation therapy is the definitive treatment modality and larger sample sizes within these studies are warranted to increase prehabilitation utilisation for patients undergoing radiation therapy.
PUBLISHED
Keywords: Prehabilitation; cancer; radiation therapy; head and neck; outcomes; prehabilitation; radiation; Prehabilitation; cancer; radiation therapy